2022
DOI: 10.1186/s40337-022-00598-7
|View full text |Cite
|
Sign up to set email alerts
|

State or trait: the neurobiology of anorexia nervosa — contributions of a functional magnetic resonance imaging study

Abstract: Background The understanding of the cerebral neurobiology of anorexia nervosa (AN) with respect to state- versus trait-related abnormalities is limited. There is evidence of restitution of structural brain alterations with clinical remission. However, with regard to functional brain abnormalities, this issue has not yet been clarified. Methods We compared women with AN (n = 31), well-recovered female participants (REC) (n = 18) and non-patients (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…This comparison, when presenting sweet foods, extended the activation of the occipital regions to the hippocampus. Increased activity in occipital visual areas was also observed when comparing AN patients vs. AN-recovered patients, as demonstrated by Göller and colleagues [ 76 ]. A comparison between the two groups (AN and HC) showed that AN had higher BOLD responses compared to HC in the medial cingulate cortex (MCC), precentral gyrus (PrCG), PoCG and parietal areas and no significant group differences for the INS or AMG.…”
Section: Resultssupporting
confidence: 54%
“…This comparison, when presenting sweet foods, extended the activation of the occipital regions to the hippocampus. Increased activity in occipital visual areas was also observed when comparing AN patients vs. AN-recovered patients, as demonstrated by Göller and colleagues [ 76 ]. A comparison between the two groups (AN and HC) showed that AN had higher BOLD responses compared to HC in the medial cingulate cortex (MCC), precentral gyrus (PrCG), PoCG and parietal areas and no significant group differences for the INS or AMG.…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, although studies have identified neurochemical changes in the brain during severe disease (15), biological markers for objectively identifying SE-AN are lacking (16).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst the relationship between structural brain differences and psychopathology remains uncertain, Walton et al's suggestion of a possible link between effects in the superior and inferior parietal gyrus to alterations in attention and "body-environment integration" is intriguing and complements a growing body of work on cognitive deficits in individuals with extremely low BMI (32).…”
Section: Is Harm Reduction Ethical?mentioning
confidence: 99%
“…Furthermore, whether the potential neural changes in response to food stimuli endure in individuals with a history of AN following weight restoration and symptom remission (REC) is still a matter of debate. While some studies propose that a reduced activity across diverse brain regions is present and persists in REC 9 and can be viewed as a trait factor, others suggest that alterations in neural responses to food stimuli observed during the acute phase of AN do not persist into the recovery phase 10 , thus representing a state phenomenon.…”
Section: Introductionmentioning
confidence: 99%